2022
DOI: 10.3390/foods11142080
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Drying Methods on the Volatile Compounds of Alliummongolicum Regel

Abstract: Allium mongolicum Regel (AMR) is a traditional Mongolian food. Various drying methods play an important role in foodstuff flavor. However, the effect of different drying methods on AMR is limited. In this study, freeze drying (FD), vacuum drying (VD), and hot-air drying (HAD) were applied to dry fresh AMR to a moisture content of 8% (wet basis); headspace gas chromatography mass spectrometry was adopted to identify volatile compounds in AMR; and principal component analysis and fingerprint similarity analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This may be because when HAD and HAVD were both under thermal treatment, the increasing temperature of the samples promoted the Maillard reaction, which resulted in the similar flavor composition [ 10 ]. An earlier study by Zhang et al on Allium mongolicum Regel also found that the flavors of VD and HAD AMR samples were relatively similar but different from the FD sample [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…This may be because when HAD and HAVD were both under thermal treatment, the increasing temperature of the samples promoted the Maillard reaction, which resulted in the similar flavor composition [ 10 ]. An earlier study by Zhang et al on Allium mongolicum Regel also found that the flavors of VD and HAD AMR samples were relatively similar but different from the FD sample [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the antioxidant activity of FA was significantly lower than that of DA, indicating that drying could improve the antioxidant activity of A. mongolicum Regel. Recent studies have shown that different drying methods have a significant effect on the degree of retention of the volatile components of A. mongolicum Regel ( Zhang et al, 2022 ), but there is no literature on the effect of drying on the antioxidant activity of A. mongolicum Regel. Interestingly, we found similar findings in the cash crop walnut, where drying increased the TPC and TFC content of walnut kernels and improved their antioxidant activity ( Wang et al, 2022 ; Wu et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…DA can also be widely added to animal feed as a growth promoter ( Ding, Liu, Erdene, Du, & Ao, 2021 ; Liu & Ao, 2021 ) and can be used in small quantities as a food seasoning ( Hithamani & Srinivasan, 2016 ), and even to extend the shelf life of sausages ( Zhao et al, 2022 ) and sheep meat ( Liu et al, 2022 ) because of its antioxidant activity. Drying A. mongolicum Regel leaves reduces their moisture content to a safe level, overcoming the disadvantages of FA leaves, which are seasonal, difficult to store and cannot be consumed year-round ( Zhang, Cao, Li, & Wang, 2022 ). Currently, the main methods of drying A. mongolicum Regel leaves are daylight, hot air, microwave, convection, vacuum and freeze drying methods, mainly depending on the amount of A. mongolicum Regel powder desired ( Qu et al, 2015 ; Wang et al, 2019 ; Zhang et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty aldehydes such as 3‐(methylthio)propanal and S‐VOCs compounds in fresh truffles were not detected in dried T. indicum truffles. The difference is that during the long‐term and high‐temperature drying process, the Maillard reaction generated a large number of nitrogen‐containing heterocyclic compounds, increasing the baking odour of the truffles while previous studies have shown that during the short‐term and low‐temperature drying process, the Maillard reaction generated aldehydes (Zhang et al ., 2022a).…”
Section: Discussionmentioning
confidence: 99%